Reforming the Roots: Can Legal Challenges Transform the Crude Palm Oil Industry in Indonesia and Malaysia? - Hamzah, Rosyidi; Adinda, Fadhel Arjuna; Prasja, Teguh Rama; Shukur, Mohd Izzat Bin Mohd Abd; Wiriatma, Dodo Wiradana (Faculty of Law, Universitas Negeri Semarang, 2026)
The crude palm oil (CPO) industries in Indonesia and Malaysia, two of the world’s leading producers, are confronted with persistent legal challenges concerning environmental sustainability, land tenure, and labor rights. Even though there is more global attention and pressure for sustainable production, the laws and regulations in Indonesia and Malaysia are still disorganized and often not strong enough to address the negative environmental and social effects of the crude palm oil industry. This paper critically examines the effectiveness of existing legal instruments and resommends comprehensive, enforceable reforms to align national practices with evolving global sustainability standards. This paper analyzes the legal challenges within the CPO sector and explores potential law reforms to enhance the industry’s sustainability and ethical standards. By conducting a comparative analysis of Indonesian and Malaysian legal systems, the study identifies gaps in regulatory enforcement, the role of multinational corporations, and the influence of international trade agreements. The urgency of this research is underscored by escalating environmental degradation, human rights violations, and the growing demand for corporate accountability—issues that threaten the long-term viability of the CPO industry. The global shift towards sustainable sourcing has intensified scrutiny of palm oil production, highlighting the need for robust legal reforms to balance economic growth with environmental and social responsibility. This research not only helps clarify the current legal landscape but also provides critical recommendations for reforms that align the industry with global sustainability goals. By exploring both countries’ legal practices, the study aims to serve as a catalyst for policymakers, legal practitioners, and industry stakeholders to rethink and reshape regulatory frameworks, ensuring a more sustainable and equitable future for the CPO industry.